An aircraft position updating based algorithm for single runway scheduling with normal and alternate aircrafts. (6th June 2023) - Dou, Hong-Da; Wang, Feng; Pan, He; Wang, Yi-Fan; Chung, Tsui-Ping
This paper investigates the problem of scheduling normal and alternate landing aircrafts at a single runway on Changchun Longjia International Airport. Usually, if the destination airport does not satisfy the landing conditions, then the aircraft has to use an alternate airport. Both normal and alternate landing aircrafts arrive at a fixed time window. Meanwhile, safety interval of adjacent landing aircrafts depends on their sizes. An integer programming model is proposed to minimise the landing completion time. Since the problem is NP-hard, an aircraft position updating based algorithm is proposed. To evaluate the performance of the proposed algorithm, a real case from Changchun Longjia International Airport and randomly generated problem instances are tested. The results show that the proposed algorithm has a better performance than the first-come first-served order and the landing constraints-based heuristic algorithms.